Volatility of LQ45 Index Situation Before and After Eid al-Fitr - Tiar Lina Situngkir; Nugraha Nugraha (Universitas Pendidikan Ganesha, 2021)
Many factors influence the movement of stocks on the capital market, one of which is a major event that occurs at a certain time, such as religious holiday event. This study aims to examine whether or not there is a change in the level of stock volume movement and abnormal return of stocks affected by the religious holiday event, namely Eid al-Fitr, thus affecting transactions in the capital market. The variable studied is the volume of shares that gives an idea of the number of outstanding shares traded every day and the abnormal variable return of shares is the difference between the actual return that occurs with the return of expectations. Both variables can provide information that is expected to help investors manage investment strategies at major events such as Eid al-Fitr. The data used is secondary data from the www.investing.com sites from 2013 to 2019, namely 15 days before and 15 days after Eid al-Fitr. The method used is Wilcoxon Signed Ranks test because it turns out that the processed data is not distributed normally after being tested for normality. The results of this study prove that there is no difference in the abnormal level of return of shares before and after Eid al-Fitr, and proves the hypothesis that there is a change in stock volume before and after the Eid al-Fitr event.